No Shoneen: Gaelic Games and the Athletic Hero in the Irish Periodical Press (Altre Modernità, 2019)
No Shoneen: Gaelic Games and the Athletic Hero in the Irish Periodical Pressby Elena OgliariTUTOR: Prof. Paolo CaponiPhD COORDINATOR: Prof. Maria Vittoria CalviDOCTORAL PROGRAMME in Linguistic, Literary and intercultural Studies in European and Extra-European PerspectivesUNIVERSITY: Università degli Studi di MilanoACADEMIC YEAR: 2019